2019
DOI: 10.3390/cells8030229
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Biogenesis in Ribosomopathies

Abstract: Ribosomopathies are congenital diseases with defects in ribosome assembly and are characterized by elevated cancer risks. Additionally, somatic mutations in ribosomal proteins have recently been linked to a variety of cancers. Despite a clear correlation between ribosome defects and cancer, the molecular mechanisms by which these defects promote tumorigenesis are unclear. In this review, we focus on the emerging mechanisms that link ribosomal defects in ribosomopathies to cancer progression. This includes func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 101 publications
(128 reference statements)
2
73
0
Order By: Relevance
“…In the context of ribosomal stress, NPM1 or free RPs from destabilized ribosomal subunits can directly interact with MDM2/HDM2, thereby disrupting the p53 interaction and promoting p53 protein stabilization as well as the activation of p53 downstream target genes driving an apoptotic response (for detailed reviews, see [103][104][105]). Interestingly, activation of the p53-mediated surveillance of ribosome biogenesis has been proposed to contribute to the pathophysiology of a group of diseases called ribosomopathies, which are caused by mutation of RBFs and RPs and are characterized, among others, by a higher susceptibility to develop cancer (see these excellent reviews for details on ribosomopathies [106][107][108][109][110]). As previously described, alterations of nucleolar protein and RBF expression implicated in pre-ribosome subunit maturation (NCL and NLE) or rRNA modifications (UBR2 and UBR5) cause ribosome biogenesis defects and result in p53-dependent cell cycle arrest or apoptosis in different models of ASCs and ESCs [75,78,80,92,93].…”
Section: Ribosome Biogenesis Surveillance By P53-dependent Pathways Imentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of ribosomal stress, NPM1 or free RPs from destabilized ribosomal subunits can directly interact with MDM2/HDM2, thereby disrupting the p53 interaction and promoting p53 protein stabilization as well as the activation of p53 downstream target genes driving an apoptotic response (for detailed reviews, see [103][104][105]). Interestingly, activation of the p53-mediated surveillance of ribosome biogenesis has been proposed to contribute to the pathophysiology of a group of diseases called ribosomopathies, which are caused by mutation of RBFs and RPs and are characterized, among others, by a higher susceptibility to develop cancer (see these excellent reviews for details on ribosomopathies [106][107][108][109][110]). As previously described, alterations of nucleolar protein and RBF expression implicated in pre-ribosome subunit maturation (NCL and NLE) or rRNA modifications (UBR2 and UBR5) cause ribosome biogenesis defects and result in p53-dependent cell cycle arrest or apoptosis in different models of ASCs and ESCs [75,78,80,92,93].…”
Section: Ribosome Biogenesis Surveillance By P53-dependent Pathways Imentioning
confidence: 99%
“…Considering the importance of ribosome in cell biology as a crucial and constitutive molecular machinery, it is quite puzzling that only some organs are affected while others can tolerate and compensate ribosome dysfunctions. Hence, intensive studies investigated how ribosome deficiencies can cause tissue-specific defects, and several hypotheses discussed in excellent reviews have been proposed to explain these observations [106][107][108][109][110]. While some hypotheses suggest that the activation of p53-dependent ribosomal stress upon RP deficiency (described in Section 3) may explain organ-specific dysfunctions in ribosomopathies, others suggest that phenotypes may be supported by models implying that ribosomes possess translational regulatory activities and mRNA selectivity in specific cell types.…”
Section: The Ribosome Concentration Regulates the Expression Of Specimentioning
confidence: 99%
“…This nascent ribosome-cancer connection was further consolidated by the observation of several somatic mutations affecting RP genes in various cancers such as leukemia, gastric, brain and ovarian cancers [36]. Mutations in RP genes uL18 (old nomenclature: RPL5); uL16 (RPL10); uL5 (RPL11) and eL22 (RPL22) have been observed in 20% of T-ALL, see [37] for a review.…”
Section: Ribosomal Genes Mutations In Cancermentioning
confidence: 99%
“…The study of RP expression and activity has gained growing attention in cancer research. Notably, because of the observation that inherited RP gene mutations producing dysfunctional ribosomes are associated with tissue-specific human pathologies named ribosomopathies and with a strong cancer predisposition [68]. Interestingly from the clinical point of view and in the context of translational research, it was demonstrated a long time ago that alterations in ribosome biogenesis occurring in cancer cells could easily be visualized by silver staining of the AgNOR representing several argyrophilic nucleolar proteins that are master regulators of ribosome biogenesis, including, for example, nucleolin (NCL), fibrillarin (FBL), and nucleophosmin (B23) [64,69].…”
Section: Regulation Of Ribosome Biogenesis By Rps In Cancersmentioning
confidence: 99%